High normal alanine aminotransferase is an indicator for better response to antiviral therapy in chronic hepatitis B - Cai, Chao; Shang, Wen-Xuan; Lin, En-Hua; Jiang, Yu-Chun; Chen, Hong; Xu, Ke; Chen, Lu; Chen, Rui-Cong; Cai, Yi-Jing; Lin, Ji; Cai, Ting-Chen; Lin, Xiu-Li; et al. (Frontiers in Immunology, 2024)
Background: Evidence shows people living with CHB even with a normal ALT (40U/L as threshold) suffer histological disease and there is still little research to evaluate the potential benefit of antiviral benefits in them.We retrospectively examined 1352 patients who underwent liver biopsy from 2017 to 2021 and then obtained their 1-year follow-up data to analyse.Results: ALT levels were categorized into high and low, with thresholds set at >29 for males and >15 for females through Youden's Index. The high normal ALT group showed significant histological disease at baseline (56.43% vs 43.82%, p < 0.001), and better HBV DNA clearance from treatment using PSM (p=0.005). Similar results were obtained using 2016 AASLD high normals (male >30, female >19).Further multivariate logistic analysis showed that high normal ALT (both criterias) was an independent predictor of treatment (OR 1.993, 95% CI 1.115-3.560, p=0.020; OR 2.000, 95% CI 1.055-3.793, p=0.034) Both of the models had higher AUC compared with current scoring system, and there was no obvious difference between the two models (AUC:0.8840 vs 0.8835) Conclusions: Male >30 or female >19 and Male >29 or female>15 are suggested to be better thresholds for normal ALT. Having a high normal ALT in CHB provides a potential benefit in antiviral therapy.